Keep it short: Exploring the impacts of configuration choices on the recent economics of solar-plus-battery and wind-plus-battery hybrid energy plants. (June 2022) - Montañés, Cristina Crespo; Gorman, Will; Mills, Andrew D.; Kim, James Hyungkwan
Abstract: Commercial interest in renewable-battery hybrid power plants connected to the bulk power system ("hybrids") is rapidly growing in the United States and globally. Power system planners need to anticipate the operational behavior of hybrids in order to ensure overall system reliability and planning the transmission network. However, hybrids' operational characteristics depend on underlying developer design choices, which have not been systematically explored in the literature. We fill this literature gap by computing hybrid net values across a wide range of configuration choices to evaluate trends in their development and identify factors that may alter those trends. We use historical wholesale market power prices in the seven U.S. organized wholesale power markets from 2012 to 2019 to optimize hybrid plant revenue and compute associated costs, accounting for battery degradation effects. Configuration choices modeled include battery duration, battery power capacity, size of the grid interconnection capacity relative to the generator power capacity, the size of PV panels relative to the inverter capacity, and the way that batteries and generators are coupled. We find that battery duration and battery capacity have the largest impact on the net value of solar and wind hybrids, with the most attractive hybrids having a two-hour battery duration (4–12/MWh increase in comparison to eight-hour configurations). We find that it is more attractive to set the interconnection capacity to accommodate simultaneous discharge of the generator and the battery, as opposed to limiting the interconnection capacity to the generator power rating, particularly for solar hybrids in the ERCOT and SPP markets (8–11/MWh increase). We show that our analytical results align with current commercial trends, suggesting that our net value framework can be used to understand both recent hybrid development activity and near-future trends in configurations of hybrids. Graphical abstract: Unlabelled Image Highlights: Calculate hybrid net value across a range of wind and solar hybrid configurations. Battery duration and capacity have the largest impact on the net value of hybrids. Most attractive hybrids have a two-hour battery duration. Market-specific dynamics can help explain differences in optimal battery sizing. Economic framework helps to understand commercial hybrid development activity.